Controlling emitting dipole orientations by N^O-ancillary electronic effects of [Ir(C^N)2(N^O)]-heteroleptic Ir(iii)-complexes towards efficient near-infrared (NIR) polymer light-emitting diodes (PLEDs). Issue 46 (16th November 2021) - Hou, Siyu; Liu, Jiaxiang; Wang, Baowen; Miao, Tiezheng; Lü, Xingqiang; Li, Wentao; Fu, Guorui; Feng, Weixu; Wong, Wai-Yeung
Abstract : For [Ir(C^N)2 (N^O)] complexes 1–3, the N^O-(L n )-induced TDM and orientation were responsible for their efficient NIR-PLEDs. Abstract : Despite the domination of conventional [Ir(C^N)2 (L^X)]-bis-heteroleptic iridium(iii )-complexes with NIR-phosphorescence (NIR = near-infrared) as dopants for reliable NIR-OLEDs/PLEDs (organic/polymer light-emitting diodes), the achievement of high performance remains a real challenge. In this study, taking Hiqbt (1-(benzo[ b ]-thiophen-2-yl)-isoquinoline) as the C^N ligand and one of the asymmetric Schiff-base ligands with different electronic effects as the N^O-ancillary ligand, three novel C 1 -symmetric [Ir(C^N)2 (N^O)]-bis-heteroleptic iridium(iii )-complexes 1–3 were developed. With contributions from the TDM (transition dipole moment) and the emitting dipole orientation induced by the N^O-ancillary electronic effects, the doped NIR-PLEDs-1–3 exhibited attractive high efficiency ( η maxEQE = 3.3–5.6%; λ em = 708–712 nm) apart from the almost negligible (<5%) efficiency roll-off. This finding shows that for typical [Ir(C^N)2 (L^X)]-bis-heteroleptic iridium(iii )-complexes, apart from the (L^X)-incorporated electronic effects on the HOMO–LUMO gap, the L^X-induced TDM vector and the molecular orientation effects on the Φ PL and the η out (25–29%) should be further taken into account, especially in challenging the intrinsic low NIR-phosphorescent efficiency of their [Ir(C^N)2 (L^X)]-bis-heteroleptic iridium(iii )-complexes.